Análisis del desempeño de la potencia y el torque de un motor diésel operando con mezclas de biodiésel de palma - Herrera Susa, Daniel Andrey; Bermúdez Santaella, José Ricardo; Castilla Álvarez, Carlos Eduardo (Ingeniería, 2020)
Context: There is a trend in modern society that is based especially on the development of new biofuels, specifically oriented towards the field of internal combustion engines, establishing the loss of their thermal performance as a central point. This is one of the main challenges, where research is dynamized in a complex and important way. In this context, this research strengthens this area of knowledge and determines the performance behavior of a single-cylinder engine ignited by compression with mixtures between conventional diesel and biodiesel produced with innovative techniques. Method: In this work, an analysis was made in a test bench for Diesel internal combustion engines, where the efficiency of the engine was characterized and determined, using Diesel and different mixtures such as B2, B5, B10, B20, B50 and B100, whose number determines the percentage of biodiesel in the mixture. The employed biodiesel was based on African palm oil and was obtained by means of microwave radiation technology. These tests were performed using the SAE J1349 standard. Data collection of factors such as power, torque, fuel consumption, and temperature, indicated engine performance, which in turn determined the effects of the different fuels under study. Results: During the development of the tests and their analysis, it was evidenced that, for all the analyzed mixtures, combustion took place without complications. Additionally, when the percentage of biofuel in the mixture, fuel consumption reported increases greater or equal to 20 %, as well as power losses in the range of 40 %. Therefore, the use of microwave technology was shown to be more efficient for production. Conclusions: With the applied methodology, it was determined that, for the B20 mixture, power values were the most stable in terms of thermal efficiency. In the context of the comparison of standard fuels, Colombian and Venezuelan diesel, under the same operating conditions, it was seen that the Venezuelan diesel-type fuel has better performance characteristics in terms of power, torque, and thermal stability. With respect to the specific consumption of the obtained fuel, the increase is observed with a higher percentage of biodiesel mixture, this being directly proportional to power loss.